2021
DOI: 10.1038/s41467-021-24890-3
|View full text |Cite
|
Sign up to set email alerts
|

Compounds targeting OSBPL7 increase ABCA1-dependent cholesterol efflux preserving kidney function in two models of kidney disease

Abstract: Impaired cellular cholesterol efflux is a key factor in the progression of renal, cardiovascular, and autoimmune diseases. Here we describe a class of 5-arylnicotinamide compounds, identified through phenotypic drug discovery, that upregulate ABCA1-dependent cholesterol efflux by targeting Oxysterol Binding Protein Like 7 (OSBPL7). OSBPL7 was identified as the molecular target of these compounds through a chemical biology approach, employing a photoactivatable 5-arylnicotinamide derivative in a cellular cross-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
36
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 41 publications
(37 citation statements)
references
References 60 publications
1
36
0
Order By: Relevance
“…Moreover, the cardiolipin peroxidase inhibitor elamipretide ameliorates both albuminuria and podocyte loss in mice with established DN [ 257 ]. Small molecule drugs that up-regulate ABCA1-dependent cholesterol efflux by targeting oxysterol efflux by targeting oxysterol-binding protein-like 7 (OSBPL7) normalise proteinuria and prevent renal function decline in both adtiamycin-induced nephropathy and Alport Syndrome [ 289 ].…”
Section: Mechanisms Of Podocyte Injurymentioning
confidence: 99%
“…Moreover, the cardiolipin peroxidase inhibitor elamipretide ameliorates both albuminuria and podocyte loss in mice with established DN [ 257 ]. Small molecule drugs that up-regulate ABCA1-dependent cholesterol efflux by targeting oxysterol efflux by targeting oxysterol-binding protein-like 7 (OSBPL7) normalise proteinuria and prevent renal function decline in both adtiamycin-induced nephropathy and Alport Syndrome [ 289 ].…”
Section: Mechanisms Of Podocyte Injurymentioning
confidence: 99%
“…These compounds cause significant hearing loss in humans ( 37 ) necessitating the identification of alternate means to stimulate cholesterol efflux. Recently small molecules have been identified that activate ATP-binding cassette transporter (ABCA1)-mediated cholesterol efflux via targeting Oxysterol Binding Protein Like 7 (OSBPL7) ( 38 ). This approach also ameliorated Alport kidney disease progression and increased lifespan by about 20%.…”
Section: Alport Glomerular Disease Progressionmentioning
confidence: 99%
“…As the major regulator of cholesterol efflux in podocytes, ABCA1 deficiency is associated with podocyte lipid accumulation in glomerular diseases such as diabetic kidney disease (DKD), FSGS and Alport syndrome [ 48 , 49 , 50 ]. Using a pharmacological ABCA1 inducer in db/db mice, we demonstrated a significant reduction in cholesterol ester content in the kidney cortices in association with improved renal function [ 48 ].…”
Section: Potential Therapeutic Targetsmentioning
confidence: 99%
“…In another study, we demonstrated that promoting ABCA1-mediated cholesterol efflux similarly prevents renal disease progression in an experimental model of FSGS (adriamycin-induced nephropathy) and of Alport syndrome (Col4a3 KO mice) in association with reduced formation of lipid droplets in glomeruli and reduced accumulation of cholesterol esters in kidney cortices. Mechanistically, we showed that these compounds exercise their effect via binding to oxysterol binding protein-like 7 (OSBPL7), opening the possibility that OSBPL7 could be a novel therapeutic target [ 49 ].…”
Section: Potential Therapeutic Targetsmentioning
confidence: 99%